Black Adolescent Females' Perceptions of Racial Discrimination When Accessing Reproductive and General Health Care. (September 2016) - Lewis, Valerie J.; Mollen, Cynthia J.; Forke, Christine M.; Peter, Nadja G.; Pati, Susmita; Medina, Sheyla P.; Johnson, Sarah E.
Adolescents, like adults, frequently experience discrimination, which can be particularly salient in the context of reproductive health care. We examined urban Black adolescent females' perceived experiences of racial discrimination during reproductive health care encounters. Structured face-to-face interviews were conducted with female African American patients, from age 13 through 20, who obtained reproductive health care services at a single site. Twenty-four participants were enrolled. All were in or graduated from high school, with a mean age of 16.8 years. These young Black women reported infrequent race-based discrimination in the health care setting; however, many reported commonly experiencing discrimination in other places. An awareness of the discrimination that minority young women experience in non–health care settings can help providers demonstrate cultural humility when addressing such concerns with their patients. With this information, providers can provide anticipatory guidance and the tools necessary to navigate complex social systems.